Polycyclic aromatic hydrocarbons in the graphene era - Wang, Xiao-Ye; Yao, Xuelin; Müllen, Klaus (Science China. Chemistry, 2019)
Polycyclic aromatic hydrocarbons (PAHs) have been the subject of interdisciplinary research in the fields of chemistry, physics, materials science, and biology. Notably, PAHs have drawn increasing attention since the discovery of graphene, which has been regarded as the “wonder” material in the 21st century. Different from semimetallic graphene, nanoscale graphenes, such as graphene nanoribbons and graphene quantum dots, exhibit finite band gaps owing to the quantum confinement, making them attractive semiconductors for next-generation electronic applications. Researches based on PAHs and graphenes have expanded rapidly over the past decade, thereby posing a challenge in conducting a comprehensive review. This study aims to interconnect the fields of PAHs and graphenes, which have mainly been discussed separately. In particular, by selecting representative examples, we explain how these two domains can stimulate each other. We hope that this integrated approach can offer new opportunities and further promote synergistic developments in these fields.